A identidade à flor da pele. Etnografia da prática da tatuagem na contemporaneidade (2006)
ABSTRACT: This article provides a descriptive account of contemporary tattooing, based on a perspective that prioritizes the notion of practice, as well as the interactions and experiences involved in the process of being tattooed. The analysis attempts to rebuild a holistic view of tattooing, combining subjective processes and social dynamics as equally constitutive parts of this activity. Among the conclusions reached are: (a) the emergence of tattooing as a new aesthetic norm and a lived experience at the heart of the western society; and (b) the configuration of a new subjectivity, the tattooed, as an interactive, innovative, emotional and reflexive process in which the body is converted into a form of expressing and constructing the subject.